Diagnosis of female genital schistosomiasis and other genital infections in young South African women: challenges in the syndromic approach - Solrun Søfteland; Solrun Søfteland; Solrun Søfteland; Motshedisi Sebitloane; Hashini Nilushika Galappaththi-Arachchige; Hashini Nilushika Galappaththi-Arachchige; Elisabeth Kleppa; Sigve Holmen; Pavitra Pillay; Patrica Doris Ndhlovu; Myra Taylor; Birgitte Jyding Vennervald; et al. (Frontiers in Tropical Diseases, 2024)
IntroductionFemale genital schistosomiasis is a common but neglected disease, which results in symptoms similar to sexually transmitted infections in Schistosoma haematobium-endemic areas of Africa and Middle East. In primary healthcare of low-income countries, healthcare professionals use syndromic management protocols for guidance when treating symptoms of genital infection, due to lack of laboratory resources. These protocols do not include treatment for female genital schistosomiasis, despite the overlap of symptoms. Women are at risk of not receiving the appropriate treatment. The aim of this study was to investigate challenges and missed opportunities when using syndromic management protocols for sexually transmitted infections in female genital schistosomiasis-endemic areas.MethodsThis is a secondary analysis of data from a large cross-sectional prevalence study conducted in 2011 in KwaZulu-Natal, South Africa. Young women in schistosomiasis-endemic areas were asked about genital symptoms and underwent laboratory testing and gynecological examinations to look for common genital infections including female genital schistosomiasis. We used the current South African syndromic management protocols as the basis and analyzed the associations between the reported genital symptoms and the differential diagnoses with logistic regression.ResultsBy use of the syndromic approach the conditions gonorrhea, trichomoniasis and herpes could be identified. The symptom “lower abdominal pain” was significantly associated with documented female genital schistosomiasis. However, the same association was not found with gonorrhea or chlamydia. We found no significant association between reported vaginal discharge syndrome and female genital schistosomiasis or between genital ulcer syndrome and female genital schistosomiasis.DiscussionFemale genital schistosomiasis frequently co-exists with, and mimics other genital infections in rural areas of Sub-Saharan Africa. The management protocols in schistosomiasis endemic countries should include advice on how to diagnose and manage this chronic, waterborne genital condition. There is an urgent need to upscale laboratory and diagnostic resources in low-and middle-income countries and specifically schistosomiasis-endemic areas, to diagnose these common genital infections more accurately and to treat affected women accordingly.